2009
DOI: 10.3844/ajidsp.2009.68.73
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Vitex leucoxylon L. Bark Extracts Against Freund's Complete Adjuvant Induced Arthritis in Sprague Dawley Rat

Abstract: Problem statement: Anti-inflammatory agents, particularly steroids and cyclooxygenase inhibitors are often associated with adverse side effects including, GI irritation, ulcers, hypertension and cardiac abnormalities. A safe and effective intervention is essential for the treatment of inflammatory disorders. Approach: Abstract Vitex leucoxylon L., a medicinal plant of the verbenaceae family, used in traditional medicine for relieving headache and catarrh. VL-89/185A, was obtained by bio activity-guided fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
(18 reference statements)
2
7
0
3
Order By: Relevance
“…and triterpenoids produced significant antiinflammatory activities (Silva et al, 2005). The obtained anti-inflammatory results are in line with other previous studies in family Verbenaceae (Shukla et al, 2011;Amir et al, 2011;Krishnaraju et al, 2009;Monteiro et al, 2007; Penido et al, 2006; Abena et al, 2003). The anti-pyretic activity of TMEL and its fractions have been evaluated by causing reduction in yeast-induced pyrexia (Table 6).…”
Section: Resultssupporting
confidence: 87%
“…and triterpenoids produced significant antiinflammatory activities (Silva et al, 2005). The obtained anti-inflammatory results are in line with other previous studies in family Verbenaceae (Shukla et al, 2011;Amir et al, 2011;Krishnaraju et al, 2009;Monteiro et al, 2007; Penido et al, 2006; Abena et al, 2003). The anti-pyretic activity of TMEL and its fractions have been evaluated by causing reduction in yeast-induced pyrexia (Table 6).…”
Section: Resultssupporting
confidence: 87%
“…After subcutaneous inject ion, CFA induces adjuvant arthritis that can serve as a model to test the anti-arthritic and anti-inflammatory effects of investigational substances. The effect observed in this model seems to be parallel to that observed in human disease (Alluri et al, 2009;Jia et al, 2003;Newbould, 1963;Pearson and Wood, 1959).…”
Section: Introductionsupporting
confidence: 79%
“…Accumulating lines of evidence show that oxidative stress mechanism has been implicated in the pathogenesis of psychiatric and brain disorders (Krishnaraju et al, 2009). Recently, numerous studies demonstrated that substance possessing antioxidant activity could reduce psychiatric symptoms and improve cognitive function (Jittiwat et al, 2009;Hasan et al, 2009;Phachonpai et al, 2010;Tong-Un et al, 2010a;2010b;2010c).…”
Section: Introductionmentioning
confidence: 99%